2011
DOI: 10.1097/ftd.0b013e3182241799
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 6 Glucocorticoids in Human Plasma by Liquid Chromatography Tandem Mass Spectrometry: Method Development, Validation, and Assessment of Matrix Effects

Abstract: A validated, sensitive, selective, and reproducible method for quantifying the concentrations of 6 glucocorticoids in human plasma by liquid chromatography tandem mass spectrometry is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Serum concentrations of etonogestrel were measured using a validated ultra‐performance liquid chromatography/tandem mass spectrometry (UPLC/MS‐MS) method. The method was developed at the Department of Clinical Pharmacology, University Hospital of Linköping, from a method previously described by Seaves et al Detailed information on the method is found in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Serum concentrations of etonogestrel were measured using a validated ultra‐performance liquid chromatography/tandem mass spectrometry (UPLC/MS‐MS) method. The method was developed at the Department of Clinical Pharmacology, University Hospital of Linköping, from a method previously described by Seaves et al Detailed information on the method is found in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…We used a validated ultraperformance liquid chromatography/tandem mass spectrometry method (UPLC/MS-MS) to measure the serum concentrations of LNG. The method was developed at the Department of Clinical Pharmacology, University Hospital of Linköping, from a method previously described by Seaves et al [25]; this method was used in a previous study comparing desogestrel in women before and after RYGB [17]. The present study was performed in a very similar design, but no participants or result overlap between the studies.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel experiments methylprednisolone (1000 μ g/L) was added or not to the combined treatment of tacrolimus and sirolimus for 24 hours at 37°C (5% CO 2 ). We used our previous investigation into the blood through concentrations of methylprednisolone after a bolus dose of 500 mg intravenously in liver transplant recipients, to select the dose to use in in vitro exposure [ 22 , 23 ]. We have also shown that 48 hours use of different doses of methylprednisolone to human islets in vitro reduced the viability and insulin secretion, without representing a durable detrimental effect [ 19 ].…”
Section: Methodsmentioning
confidence: 99%